The Synergetic Effect of Emotions on the Travel Motivations of Senior Tourists - Pestana, M.H.; Luiz Moutinho; Paul Phillips, (NEW CHALLENGES, STRATEGIES AND TRENDS IN TOURISM, HOSPITALITY AND MANAGEMENT, 2016)
This paper seeks to make three contributions to the senior tourism literature. The first is the identification of how positive and negative emotions affect motivational push and pull factors; the second is the determination of how to keep this consumption segment attractive; and the third is the identification and measurement of travel motivations as mediators through a study involving senior tourists . A survey of 464 senior tourists vacationing in Lisbon was conducted using exploratory factorial analysis in the pre-test stage, and structural equations modeling in the survey stage. The results reveal that emotions play an important role in the comprehension of senior tourists’ travel motivations. Senior tourists manifesting psychological well-being attach more importance to pull factors, and are less satisfied with their holidays than those who attach more importance to push factors. Tourism organizations should, therefore, be prepared to reimagine and overcome some pre-conceived ideas about this affluent segment.